Design of a novel pH sensor for flap monitoring and evaluation of its efficacy in an in vivo flap model - Yalcin, Can Ege; Yilmaz, Vildan; Arslan, Hakan; Yuksel, Sureyya Aydin (ELSEVIER SCI LTD, 2025)
Purpose: This study aimed to design a novel pH sensor for free flap monitoring and to evaluate its efficacy in a preliminary animal model, with the goal of supporting earlier detection of perfusion changes. Materials and methods: The study was conducted in two phases. First, the sensor was designed, fabricated, and validated through in vitro testing. In the second phase, 15 Sprague-Dawley rats were divided into three groups based on the type of vascular occlusion: arterial, venous, or total pedicle. A superficial inferior epigastric island flap was elevated in each animal, and the sensor was placed beneath the flap. Continuous measurements were recorded for baseline, occlusion, recovery, and repeat occlusion phases, each lasting 20 minutes. Results: Arterial and venous occlusions produced characteristic current signal peaks, whereas pedicle occlusion resulted in irregular, noisy readings. The mean response times were 104.8, 130, and 170 seconds for the arterial, venous, and pedicle groups, respectively. Conclusion: In this pilot study, the novel pH sensor detected changes in current output following vascular occlusion in a rat flap model. These findings suggest potential for use in free flap monitoring. Further development is needed to produce biocompatible, wireless, and clinically applicable versions for human use. (c) 2025 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Microsurgery; PH sensor; Free flap monitoring; Arterial occlusion; Ischemia; Venous occlusion; ISCHEMIA-REPERFUSION INJURY; SUBCUTANEOUS TISSUE PH; MUSCLE; Surgery